Approach for the Design of a Broadband Microwave Power Amplifier in Microstrip Technology for Mobile Communications Systems - Mohammed LAHSAINI; Lahbib ZENKOUAR; Adil SAADI (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2020)
This work presents a broadband power amplifier in S-band in microstrip technology. The proposed power amplifier is modeled with a single-stage architecture based on a field effect transistor ATF13786 of Agilent Technologies (hp)®. The used transistor has been polarized with transmission lines and it has been adapted with matching networks in the form of λ/4 transformers filters at the input and at the output. This amplifier has been studied and optimized using the Advanced Design System (ADS®) software. The simulation results of the output power and S parameters show excellent characteristics with a satisfactory gain greater than 10.9 dB, low reflections, a saturated output power of 16.4 dBm with a 1 dB compression point at an input power level of about 5 dBm, a maximum PAE of 25.3% and unconditional stability in the desired frequency band. The modeled amplifier can be integrated into mobile communications systems namely LTE mobile networks (2500 to 2690 MHz) and wireless networks using Wi-Fi protocol (2400 to 2485 MHz).